Maturation of Airway Defensive Reflexes Is Related to Development of Feeding Behavior during Growth in Rabbits - Coutier-Marie, Laurianne; Ioan, Iulia; Bonabel, Claude; Demoulin, Bruno; Leblanc, Anne-Laure; Debitu, Ludivine; Schweitzer, Cyril; Marchal, François; Demoulin-Alexikova, Silvia (Frontiers in Physiology, 2017)
Introduction. Cough and expiration reflex are major lower airway defense mechanisms that have not been studied throughout development in relation with the feeding behavior. Aim: To describe airway defense reflexes evoked by mechanical stimulation of the trachea in developing rabbit pups. Material and Methods. Sixty one pups were allocated to 3 groups according to their feeding behavior: suckling (n = 22), weanling (n = 21) and weaning (n = 18) group. The incidence and sensitivity of defense reflexes triggered by mechanical tracheal stimulation were studied in anesthetized and tracheotomized animals. Data are expressed as median (25th to 75th percentile). Results. The overall incidence of defensive responses (cough and/or expiration reflex) was found to be significantly higher in suckling (100% (50-100%); p = 0.01) and weanling (75% (40-100%); p = 0.05] animals when compared to weaning ones (37.5% (0-75%). However, cough motor pattern accounted for only 29% (0-62%) of all defensive responses in suckling rabbits and its frequency was significantly lower in this group when compared with weanling (100%(50-100%); p=0.006] or weaning group [62%(50 – 100%), p=0.05]. In other word the expiration reflex was the dominant response in suckling animals. Conclusion. Incidence and motor pattern of defensive responses were found to be linked to the pup feeding behavior and the expiration reflex was the major response triggered in suckling pups. The results suggest that this reflex is especially fitted to occur during the coordinated swallowing - breathing fast activities of sucking.